Identity and territory Jewish perceptions of space in antiquity - Ben-Eliyahu, Eyal; University of California Press (Berkeley, CA University of California Press, 2019)
Frontmatter -- Contents -- Illustrations -- Preface -- Introduction -- 1. From Judah to Israel: Territory and Identity -- 2. Borders, Space, and Identity in Second Temple Literature -- 3. From Earthly Land to Holy Land -- 4. Land of the Sages -- 5. Rabbinic Literature Confronts Nonrabbinic Jewish Culture and Christianity: The Question of Holy Spaces -- Conclusion -- Bibliography -- Index of Places -- Index of Sources -- Index of Persons -- Index of Subjects
Throughout history, the relationship between Jews and their land has been a vibrant, much-debated topic within the Jewish world and in international political discourse. Identity and Territory explores how ancient conceptions of Israel—of both the land itself and its shifting frontiers and borders—have played a decisive role in forming national and religious identities across the millennia. Through the works of Second Temple period Jews and rabbinic literature, Eyal Ben-Eliyahu examines the role of territorial status, boundaries, mental maps, and holy sites, drawing comparisons to popular Jewish and Christian perceptions of space. Showing how space defines nationhood and how Jewish identity influences perceptions of space, Ben-Eliyahu uncovers varied understandings of the land that resonate with contemporary views of the relationship between territory and ideology
[Online-Ausg.]
Mode of access: Internet via World Wide Web.
In English
Keywords: Jews -- Identity -- History -- To 1500; Judaism -- History -- Post-exilic period, 586 B.C.-210 A.D; Space -- Religious aspects -- Judaism; HISTORY / Ancient / General; RELIGION / Ancient; Religion / Judaism / History; jewish identity; jewish; judaism; boundaries; contemporary; debate; global; government; holy land; holy sites; ideology; international; israel; jewish history; jewish holy land; jewish holy sites; jews; land boundaries; land ownership; land rights; maps; nationhood; political discourse; politics; rabbi; rabbinic literature; religion; religious identities; religious identity; religious studies; second temple period; territory; worldwide